Variación de ritmos circadianos, patrón alimentario y estado nutricional de adultos de los distritos de Punchana, Belén, San Juan Bautista e Iquitos, 2024 - Rodriguez Quiroz, Ivis Aynae (2025)
The objective of the research was to evaluate the relationship between the variation of circadian rhythms through the quality of sleep, the dietary pattern and nutritional status of adults in the districts of Punchana, Villa Belen, San Juan Bautista and Iquitos in 2024. The methodology was quantitative, non experimental, descriptive, with correlational and cross-sectional design. The sample included 1463 adults between 18 and 59 years of age. Data were collected through validated questionnaires, such as the Pittsburg Test for sleep quality, food frequency surveys and standardized anthropometric measurements. The results revealed a high prevalence of poor sleep quality in all districts, with Iquitos leading (71.1%). In terms of dietary pattern, San Juan (58%) and Belen (57.7%) presented a higher proportion of healthy patterns, a significant percentage of the population in Punchana and Iquitos reported unhealthy and unhealthy patterns. In nutritional status, overweight predominated in all districts, especially in Belen (43.5%), and type I obesity was more prevalent in Iquitos (43.5%), more prevalent in Iquitos (25.9%). Correlation analysis showed significant associations between sleep quality, dietary pattern and nutritional status, highlighting stronger relationships with indicators such as waist-hip index (WHI) and abdominal circumference (ABP). It is concluded that these variables should be addressed together to mitigate the risks associated with chronic diseases in this population.